IL-7 and IL-8 inhibit gamete interaction in the zona-free hamster egg sperm penetration assay - H. Lambert; I. Collazo; A. Steinleitner (Hindawi Limited, 1992)
Current thought in reproductive endocrinology suggests hat endometriosis-associated subfertility may be the result of an adverse influence of activated immunocompetent cells on fertilization and embryo development. Inflammatory ediators such as interleukin-1 and tumour necrosis actor have been implicated in the pathophysiology of this process. The purpose of this study was to assess the effect of two recently characterized cytokines, interleukin-7 (IL-7 ) and interleukin-8 (IL-8), on gamete interaction in the perm penetration assay (SPA). Donor sperm were preincubated or 4 h with 0.5, 5, 50, or 500 ng ml-1 of human ecombinant IL-7 or IL-8. Sperm penetration was determined by an experienced gametologist by the presence of decondensed sperm heads or pronuclei formation. A dose-dependent inhibition of gamete interaction was observed following coincubation with either IL-7 or IL-8. These data offer the possibility that IL-7 and IL-8 may play a role in the pathogenesis of immunocompetent cell-associated subfertility.